2020
DOI: 10.3389/fneur.2020.00672
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, Clinical Characteristics, and Management of Idiopathic Intracranial Hypertension in Kuwait: A Single-Center Experience

Abstract: Background: Idiopathic intracranial hypertension (IIH) affects predominantly obese females during their reproductive age period. The demographics of this condition has not been studied in Kuwait before. Objectives: To determine the demographics, clinical features, risk factors, and treatment modalities of IIH in the main neurology tertiary referral hospital in Kuwait and to compare our data with literature. Methods: A retrospective study was conducted to identify cases of IIH seen between January 1, 2018, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…11 Similar to previous studies, female predominance was found in our IIH patients. 10,14 Despite similar risk factors and age-group, female preponderance was found among IIH patients in the study of Bruce et al 15 Hormonal etiology could be a predisposing factor for IIH in the female during the fertility period. Previous studies had shown an association of OCP and IIH which was not found to be related in a recent study by Kilgore et al 16 Headache characteristics in IIH are nonspecific.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…11 Similar to previous studies, female predominance was found in our IIH patients. 10,14 Despite similar risk factors and age-group, female preponderance was found among IIH patients in the study of Bruce et al 15 Hormonal etiology could be a predisposing factor for IIH in the female during the fertility period. Previous studies had shown an association of OCP and IIH which was not found to be related in a recent study by Kilgore et al 16 Headache characteristics in IIH are nonspecific.…”
Section: Resultsmentioning
confidence: 84%
“…However, most of the previous studies have shown the positive relation of IIH with higher BMI and weight gain. 5,[10][11][12] Majority of our patients had BMI>25, however, none had BMI >30. Our results were similar to Kim et al, in contrast to western studies where the obesity percentage in IIH was higher.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The incidence of IIH has been reported to be approximately 0.03-2.36/100 000 in a recent meta-analysis, however marked heterogeneity was noted. 6 There is significant regional variation in incidence, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] with rates from as low as 0.03/100 000 in Japan 36 Open access 3.6/100 000 in Fife (Scotland). 37 Higher incidence rates are consistently reported in women, particularly women of childbearing age, 18-20 22 23 25 28-31 with the highest rates reported in women with obesity.…”
Section: Introductionmentioning
confidence: 99%